The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jso.24763
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic counseling and testing in newly diagnosed breast cancer: Patients’ and health professionals’ attitudes, experiences, and evaluation of effects on treatment decision making

Abstract: RGCT is viewed as helpful for newly diagnosed high-risk BC patients in choosing their primary surgery and should be offered routinely by surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Early studies found high anxiety amongst women tested within 1 year of breast cancer diagnosis [63] and concern amongst health professionals and patients about the timing of testing [64]. However, studies investigating actual and hypothetical experiences of genetic testing shortly after diagnosis have found that, for the most part, patients and health professionals consider this type of genetic testing to be acceptable and desirable for decision-making if treatment options are improved as a result [65, 66].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found high anxiety amongst women tested within 1 year of breast cancer diagnosis [63] and concern amongst health professionals and patients about the timing of testing [64]. However, studies investigating actual and hypothetical experiences of genetic testing shortly after diagnosis have found that, for the most part, patients and health professionals consider this type of genetic testing to be acceptable and desirable for decision-making if treatment options are improved as a result [65, 66].…”
Section: Discussionmentioning
confidence: 99%
“…When referral does take place, it is often made after definitive surgery or with insufficient time to receive test results prior to surgery. For example, many breast surgeons report that they would not delay surgery to wait for the results of a genetic test [23 24]. Thus, while appropriate referral to genetic counseling is critical, it is also critical to provide rapid access in order to maximize the value of testing without causing treatment delay.…”
Section: Introductionmentioning
confidence: 99%
“…Studies, such as the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) (Plaskocinska et al 2016 ), the DNA-BONus study (Høberg-Vetti et al 2016 ), and others (Augestad et al 2017 ; Meiser et al 2016 ; Wevers et al 2015 /Wevers et al 2016 ) have examined the acceptability and feasibility of TFGT among participants, in order to inform future roll-out of TFGT in clinical practice. Key findings from this research indicate that TFGT is commonly acceptable to patients who appreciate the treatment implications of timely testing (Gleeson et al 2013 ; Meiser et al 2012a /Meiser et al 2012b ; Wevers et al 2017 ). There is little evidence that TFGT is linked to adverse psychological effects (Høberg-Vetti et al 2016 ; Wevers et al 2015 /Wevers et al 2016 ), although studies have recommended that care should be taken to ensure that patients are treated with care and sensitivity when implementing TFGT (Augestad et al 2017 ; Shipman et al 2017 ).…”
Section: Introductionmentioning
confidence: 87%
“…Qualitative studies have focused on the information needs and experiences of ovarian cancer patients who underwent TFGT as eligibility criteria for PARP inhibitor trials (Gleeson et al 2013 ; Meiser et al 2012a ). Other studies have assessed patients’ information preferences when offered TFGT; trialing streamlined methods of information dissemination (Quinn et al 2016 ), comparing patients’ views of written information versus face-to-face communication (Meiser et al 2012b ), and examining timing preferences in relation to treatment decision-making (Wevers et al 2017 ). Studies, such as the Genetic Testing in Epithelial Ovarian Cancer (GTEOC) (Plaskocinska et al 2016 ), the DNA-BONus study (Høberg-Vetti et al 2016 ), and others (Augestad et al 2017 ; Meiser et al 2016 ; Wevers et al 2015 /Wevers et al 2016 ) have examined the acceptability and feasibility of TFGT among participants, in order to inform future roll-out of TFGT in clinical practice.…”
Section: Introductionmentioning
confidence: 99%